Профилактическая стоматология - неотъемлемый компонент стоматологической помощи населению (Эндодонтия Today)
Oral diseases prevalence remains rather high among population in most Russian regions. In such situation prevention of widespread oral diseases should be a priority of oral health services. Complex preventive program providing the differentiated approach based on age and oral condition of patients is developed in Moscow State University of Medicine and Dentistry. It is expected that systematic realization of the program will allow to decrease oral diseases prevalence on population level.